Sistem Konstruksi Berbasis Kayu : Landa’ Sebagai Studi Kasus - Muhammad Rusdin Jumurdin; Muhammad Uliah Shafar (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Wood is a superior choice as the main material for forming the structure of a construction system. Its unique characteristics and the fact that it can withstand gravity and lateral forces make it the first choice as a material for construction models. Landa', which functions as a rice storage house, has a unique construction system with the use of natural materials. The research was conducted by exploring how the construction system of landa' is formed from materials and materials using qualitative methods with a descriptive way of presentation. The results of the study concluded that the construction system of landa' uses a unique method by placing each part above the other to form a single unit of the landa' building, the column (pessajo) is bound by the beam (tolohna) and the addition of beams (parende) which will support the body of the landa', the body part is composed of walls (rinding) and fastened with a locking system tallu boko' and sa'pi’ which will support the roof (dea).